Kondisi Terumbu Karang di Pulau Sembilan Kabupaten Sinjai Sulawesi Selatan - Suharyanto Suharyanto; Utojo Utojo (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
Sembilan Island waters is one of the catch fishery production centers in Bone Bay, South Sulawesi. It was informed that the capture has decreased since 1999, which might be caused by  coral reef damage although the damage precentage was still unknown. An observation on coral reef condition was conducted in the waters of Sembilan Island, South Sulawesi, on June and November 2000 using scuba diving set and under water writing tools. Monitoring of coral reef condition was conducted in 7 m depth up to 100 m length of shore line in seven stations employing a line intercept transect method. The data of coral reef were analysed by using dBase III and lifeform programs. The results showed that living coral around station I, III, and IV were generaly in good condition except in the stations V, VI and VII, which were in middle condition and in station II, which was in bad condition. The lifeform of coral reef in Sembilan Island were predominated by Acropora Branching (ACB), Nonacropora Branching (CB), Coreal Foliose (CF), and Coral Massive (CM) meanwhile other benthic fauna were predominated by Soft Coral (SF) and Sponge (SP).